DIFFERENCES IN BODY WEIGHT BEFORE AND AFTER THE USE OF HORMONAL CONTRACEPTIVE INJECTION DEPO MEDROXY PROGESTERONE ACETATE (DMPA) IN PMB GUNARTI BANJARBARU SOUTH KALIMANTAN IN 2018 - Darmayanti Wulandatika; Siti Fatimah (LPPM - Universitas Muhammadiyah Banjarmasin, 2018)
According to the World Population Data Sheet, in 2016 Indonesia ranked 4th as the country with a population of 259 million people. Among ASEAN countries, Indonesia with the largest area remains the country with the largest population far above the nine other member countries. Coverage of fertile age couples (PUS) based on Family Planning membership according to 2017 Indonesian Family Profile and 2018 BKKBN, South Kalimantan Province in 2017 had as many as 646,374 fertile age couples, and 70.10% or as many as 453,089 actively engaged with Family Planning program. Out of total active participants obtained as much as 50.67% or 229,579 using birth control injections, 62% of them are married women, 15-49 years old used a contraceptive method and found that 58% used modern contraceptive methods, injected birth control is the most widely used contraceptive method, followed by pills. The use of birth control injections, both monthly or three monthly contraceptive injections has a main side effect - body weight changes. The factor that can trigger changes in the body weight of the acceptors of birth control injections is the presence of a strong progesterone hormone. The purpose of this study is to analyze the differences in body weight before and after the use of hormonal contraceptive injection Depo Medroxy Progesterone Acetate (DMPA) in PMB Gunarti Banjarbaru South Kalimantan in 2018. The numbers of respondents in this study were 60 respondents. Data collection was carried out using medical record data. The data were analyzed quantitatively with comparative study method, two mean dependents (paired sample) to test the mean’s difference between groups of data. Statistical test results showed that the average respondent's body weight before using hormonal contraceptive injection Depo Medroxy Progesterone Acetate (DMPA) was 53.25 Kg and the average body weight after using hormonal contraceptive injection Depo Medroxy Progesterone Acetate (DMPA) was 57.08 Kg. This can be interpreted that the range between before and after using hormonal contraceptive injection Depo Medroxy Progesterone Acetate (DMPA) is 3.87 with a standard deviation of 2.52. The result of statistical tests using the t test gets p value of 0,000. It can be concluded that there is a significant difference between before and after using hormonal contraceptive injection.